2018
DOI: 10.1002/ange.201807463
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium‐assistierte Aktivierung von Palladium zur Steigerung der Produktion von Synthesegas in der Trockenreformierung von Methan

Abstract: Kohlenstoff-gesättigte Pd 0 -Nanopartikel mit ausgedehnter Phasengrenzez uZ rO 2 bilden sich unter CH 4 -Trockenreformierbedingungen aus einem intermetallischen Pd 0 Zr 0 -Präkatalysator.D er resultierende,h ochaktive Katalysatorzustand arbeitet bifunktionell:C O 2 wird an oxidischen Phasengrenzplätzen effizient aktiviert, und Pd x Cgewährleistet die rasche Versorgung der Phasengrenzem it reaktiven C-Atomen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…From a fundamental viewpoint, these materials are of high interest as the findings on those systems can help to elucidate mechanistic insights and help to transfer the particular coking resilience to less costly, non-noble metal catalysts. In an in situ near-ambient pressure (NAP)-XPS study of our group, the anticoking stability and carbonconverting role of the Pd/ZrO 2 phase boundary (in the following denoted as PB) were highlighted [15]. The results showed that carbon-saturated Pd 0 nanoparticles evolve from an in situ activated PdZr intermetallic precatalyst, leading to the formation of extended C-saturated Pd-metal/Zr-oxide phase boundaries under methane dry reforming conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a fundamental viewpoint, these materials are of high interest as the findings on those systems can help to elucidate mechanistic insights and help to transfer the particular coking resilience to less costly, non-noble metal catalysts. In an in situ near-ambient pressure (NAP)-XPS study of our group, the anticoking stability and carbonconverting role of the Pd/ZrO 2 phase boundary (in the following denoted as PB) were highlighted [15]. The results showed that carbon-saturated Pd 0 nanoparticles evolve from an in situ activated PdZr intermetallic precatalyst, leading to the formation of extended C-saturated Pd-metal/Zr-oxide phase boundaries under methane dry reforming conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that carbon-saturated Pd 0 nanoparticles evolve from an in situ activated PdZr intermetallic precatalyst, leading to the formation of extended C-saturated Pd-metal/Zr-oxide phase boundaries under methane dry reforming conditions. The generation of these PBs results in a highly active state fostering a bifunctional mechanism by effectively activating CO 2 at the oxidic PB sites and CH 4 at the Pd 0 particles forming Pd x C, which provides a fast supply of carbon atoms toward the PB for enhanced CO evolution [15,16]. However, even if noble metals such as Pd do actually exhibit superior properties with respect to DRM activity and stability, as mentioned above, they will inevitably remain little attractive for an industrial application simply due to their high costs.…”
Section: Introductionmentioning
confidence: 99%